2009
DOI: 10.1002/ijc.24607
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 promotes cell proliferation via protein kinase C/extracellular signal regulated kinase pathway‐dependent induction of c‐Myc expression in human esophageal squamous cell carcinoma cells

Abstract: Overexpression of cyclooxygenase-2 (COX-2) and elevation of its derivative prostaglandin E 2 (PGE 2 ) are implicated in human esophageal squamous cell carcinoma. The expression of c-Myc, an oncogenic transcription factor, is also upregulated in this malignant disease. This study sought to elucidate whether a functional connection exists between COX-2/PGE 2 and c-Myc in esophageal squamous cell carcinoma. Results showed that PGE 2 substantially increased the proliferation of cultured esophageal squamous cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 38 publications
1
26
1
Order By: Relevance
“…It was found that COX-2 prevented apoptosis and was associated with inflammation, cell growth and differentiation [5]. Prostaglandins produced via COX-2 activation, including prostaglandin E2 (PGE2), are believed to be the major contributors to cell proliferation [36], and PGE2 has been regarded as a primary COX-2 product in smooth muscle cells [37]. Transfection of rat intestinal epithelial cells with COX-2 gene caused inhibition of apoptosis accompanied by increased spontaneous output of PGE 2 and increased levels of an anti-apoptotic protein Bcl-2 [38].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that COX-2 prevented apoptosis and was associated with inflammation, cell growth and differentiation [5]. Prostaglandins produced via COX-2 activation, including prostaglandin E2 (PGE2), are believed to be the major contributors to cell proliferation [36], and PGE2 has been regarded as a primary COX-2 product in smooth muscle cells [37]. Transfection of rat intestinal epithelial cells with COX-2 gene caused inhibition of apoptosis accompanied by increased spontaneous output of PGE 2 and increased levels of an anti-apoptotic protein Bcl-2 [38].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that FFSS induces PGE 2 release and PGE 2 accumulates over time in the CM collected from continuous FFSS. PGE 2 is known to activate MAPK signaling through EP 2 or EP 4 receptors (27,28). Previous studies from our laboratory and others have shown that PGE 2 signaling occurs through EP 2 and EP4 receptors in MLO-Y4 osteocytes (5, 7).…”
Section: Pge 2 Released In the CM Under Continuous Ffss Is Responsiblmentioning
confidence: 93%
“…1c) in a dose and timedependent manner. Since PGE 2 stimulates cell proliferation in vascular smooth muscle cells (Yau and Zahradka 2003) and esophageal cancer cells (Yu et al 2009), we treated cells with submicromolar concentrations of PGE 2 and measured cell proliferation by cell counting. No significant reduction or increase in cell proliferation was observed in cells treated with up to 1 lM PGE 2 (Fig.…”
Section: Induction Of Cellular Senescence By Pgementioning
confidence: 99%